Reflection Of 21ST Century Women In Sutan Takdir Alisjahbana’s Novel 'Layar Terkembang': A Semiotic Study - Sri Rahayu, Nova; Karim, Maizar; Rustam (Institut Agama Islam Negeri Palopo, 2024)
This study aims to analyze the dual roles of women in the novel Layar Terkembang by Sutan Takdir Alisjahbana and how these roles shape their character and demeanor. Method: This research employs a qualitative approach with a text analysis method. The research data is obtained from the text of the novel Layar Terkembang and analyzed using interpretation and descriptive techniques. Results: The study found that women in Layar Terkembang have dual roles, both as individuals and as members of society. These dual roles shape the women into complex, independent, and progressive characters. The characters Tuti and Maria, for instance, demonstrate courage in breaking traditions and pursuing their dreams. The dual roles of women also reflect Sutan Takdir Alisjahbana’s view on women's emancipation during his time. The novel Layar Terkembang not only portrays women as complements to the story but also as messengers conveying the role and potential of women in society. This novel encourages women to transcend traditional boundaries and actively contribute to various aspects of life.